Changes in Value Orientations Among Young People - Khachatryan, Narine; Grigoryan, Ani; Serobyan, Astghik (Bulletin of Yerevan University E: Philosophy, Psychology, 2022)
The article aimed to compare the value orientations of young people over the last 10 years in Armenia. Sh. Schwartz’s theory of basic values served as a methodological basis for the study, where ten value orientations were distinguished. The results showed that self-direction as the value of openness to change, and security as a conservation value, being emphasized in 2011, became even more important for young people in 2022. There was a visible transition in value orientations of young people from the value of achievement characterized by the aspiration of power and social dominance as self-enhancement to the universalism defined by the concern for the welfare and rights of others as a self-transcendence within the last ten years.
Keywords: value orientation; theory of basic values; values of self-enhancement, selftranscendence, openness to change and conservation; multivariate regression analysis